The Utilization of ZEP Quiz in Developing Students' Contextual Understanding of Fiqh - Lu’luul Mukarromah; Nur Azizah Riska Ayu Astiani Mahmudah (Jurnal Penelitian Medan Agama, 2026)
Fikih learning plays a crucial role in developing students' understanding of Islamic jurisprudence and its application in everyday life. However, learning practices that remain predominantly theoretical and text oriented often hinder students from comprehending Fikih concepts within authentic real life contexts. This study aims to examine students' understanding of contextual Fikih through the utilization of ZEP Quiz, identify the factors contributing to the mismatch between conventional Fikih assessment models and the demands of digital era learning, and analyze the influence of ZEP Quiz based gamification on students' engagement. This research employed a qualitative approach using a case study design conducted at MAN 1 Situbondo, involving Fikih teachers and students as the research participants. Data were collected through classroom observations, semi structured interviews, and documentation, and were analyzed descriptively based on the instructional context. The findings indicate that ZEP Quiz facilitates students' understanding of contextual Fikih by providing an interactive and enjoyable learning experience. The incompatibility of existing assessment models is primarily attributed to the dominance of conventional teacher centered approaches that emphasize rote memorization, thereby limiting the development of students' critical thinking and practical application skills. Furthermore, ZEP Quiz based gamification was found to enhance students' participation, motivation, and classroom interaction throughout the learning process. These findings highlight that the integration of gamification offers an innovative alternative for fostering more relevant and contextual Fikih learning while supporting the development of students' cognitive, affective, and psychomotor competencies in the digital era.